2017
DOI: 10.1177/1099800417699879
|View full text |Cite
|
Sign up to set email alerts
|

Testing a Resilience Training Program in Police Recruits: A Pilot Study

Abstract: Results confirm several significant effects of resilience training with recruits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…There were no significant differences between the interventions on any of the primary or secondary outcome measures at the post-intervention or follow-up timepoints although participants receiving the resilience intervention rated it as more helpful than those receiving psychoeducation. The results of this trial are consistent with findings that resilience interventions may have limited effects on mental health outcomes in emergency workers [12][13][14][15][16][17] and the growing concern in the field that although some interventions may improve wellbeing [7][8][9][10][11], it remains to be seen whether or not this translates to better mental health outcomes. Interestingly, modest improvements were observed for participants receiving psychoeducation on some outcomes at follow-up compared to their baseline assessments.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…There were no significant differences between the interventions on any of the primary or secondary outcome measures at the post-intervention or follow-up timepoints although participants receiving the resilience intervention rated it as more helpful than those receiving psychoeducation. The results of this trial are consistent with findings that resilience interventions may have limited effects on mental health outcomes in emergency workers [12][13][14][15][16][17] and the growing concern in the field that although some interventions may improve wellbeing [7][8][9][10][11], it remains to be seen whether or not this translates to better mental health outcomes. Interestingly, modest improvements were observed for participants receiving psychoeducation on some outcomes at follow-up compared to their baseline assessments.…”
Section: Discussionsupporting
confidence: 82%
“…The last few decades have seen a surge in the development of interventions aimed to improve resilience in emergency worker populations, with resilience generally being defined as the capacity to maintain wellbeing in response to adversity or stress [6]. Despite widespread use, however, there is conflicting evidence for their efficacy with some resilience interventions demonstrating improvements in wellbeing, sleep or stress symptoms [7][8][9][10][11] whilst others show no significant effects on mental or physical health outcomes [12][13][14][15][16][17]. Evaluations have typically been hampered by heterogeneity in intervention design, content and outcome measurement, and low methodological quality among studies [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In that study, the participants reported improvements with work and their personal lives. Similarly, a study of recruits in the Milwaukee Police Department (Ramey et al, 2017), also with a small sample size (n = 34), produced promising results in developing resilience. This program involved a 2-h session, instructions on breathing exercises, as well as four tele-mentor sessions spaced out over approximately 3 months in total.…”
Section: Current First Responder Resiliency Trainingmentioning
confidence: 99%
“…There is an extensive body of research showing that providing HRV coherence feedback to facilitate skill acquisition of self-regulation techniques improves a wide range of health and performance outcomes (15, 6386). …”
Section: New Frontiersmentioning
confidence: 99%
“…It has been shown that providing emotional self-regulation skills combined with heart rhythm coherence training results in significant improvements in communication, employee satisfaction, productivity, problem solving, reduced turnover, and a significant return on investment, both financially and socially (15, 67, 73, 86, 9092). In our experience, the self-regulation and resilience building training programs are most successful when leadership openly models and support the programs (93).…”
Section: Training Programs To Increase Social Coherencementioning
confidence: 99%